A Fertilization of Sweet Corn, Celery, Romaine, Escarole, Endive, and Radish on Organic Soils in Florida - George Hochmuth; Ed Hanlon; George Snyder; Russell Nagata; Tom Schueneman (EDIS)
Celery, sweet corn, endive, escarole, romaine lettuce, and radish are important crops on organic soils in Florida. This bulletin summarizes fertilization research results with these crops from the 1940s to the present. New interpretations of these compiled works were used to produce updated UF/IFAS Extension recommendations for fertilization of these six vegetable crops. The recommendations presented in this publication supersede those found in Bulletin 876 (Sanchez, 1990), Bulletin 757 (Guzman et al., 1973), Circular 806 (Hochmuth and Hanlon, 1989), and fertilization recommendations in all crop production guides printed previous to this circular.